Nuclear Level Density Parameter of 161−168Er and 204−210Bi Deforme Nuclei - Shafik, Shafik S; Flaiyh, Gaith Niama; Ali, Akram M (Al-Nahrain Journal of Science, 2018)
In present work we calculate the Level density Parameter (LDP) of 161-168Er and 204-210Bi isotopes deformated nuclei using collective enhancement including rotation ground state modes at neutron binding energy and obtained by equidistant and non equidistance method for each nucleus and compared the results with several methods and expermintal one.